Strengthening Human Resources and Digital Tourism Mapping for the Sustainability of Troso Weaving Village - Widagdo, Jati; Roosdhani, M Rifqy; Mujiyono; Aulia Pambajeng Miftahunnajah, Nimas (Jurnal Pengabdian Kepada Masyarakat MEMBANGUN NEGERI, 2025)
This community service program was conducted in Troso Weaving Village, Jepara, with the aim of addressing the challenges of generational succession, weak business management, and limited market access in the traditional weaving industry. The second year of implementation focused on three main activities: the integration of weaving knowledge into the local school curriculum, the provision of managerial and digital marketing training for artisans, and the development of a digital tourism map to promote the village as a cultural tourism destination. Data was collected through focus group discussions, training evaluations, and field surveys, while program effectiveness was measured using pre-test and post-test instruments. The results showed that the integration of weaving into local curricula created a structured pathway for cultural regeneration, ensuring that younger generations were exposed to traditional skills and local identity. Managerial and digital marketing training significantly improved artisans’ knowledge, with average scores rising from 46 percent in the pre-test to 82 percent in the post-test, particularly in financial management and digital promotion. The digital tourism map successfully identified 21 weaving houses and galleries, enabling greater visibility and easier access for tourists and buyers through QR-coded profiles. These interventions demonstrated that cultural sustainability in Troso could be achieved through a multidimensional approach that combined education, capacity building, and digital innovation. The program provided a replicable model for preserving traditional crafts while enhancing their competitiveness in the modern economy.